Modernizing the Framework for Fiscal Policy and Public Debt Sustainability Analysis. (Policy Papers; Policy Paper ;, 2011)
Modernizing the framework for fiscal policy and public debt sustainability analysis (DSA) has become necessary, particularly in light of the recent crisis and rising sustainability concerns in some advanced economies. While recognizing the inherently challenging nature of such analysis, this paper highlights areas where improvements are needed and makes both general and specific proposals on how this could be achieved. It also proposes to move to a risk-based approach to DSAs for all market-access countries, where the depth and extent of analysis would be commensurate with concerns regarding sustainability, while a reasonable level of standardization would be maintained.